EFFECTIVENESS EVALUATION SYSTEM CHANGE RATES ON TOBACCO PRODUCTS EXCISE EXCISE REVENUE (Case Study in Yogyakarta KPPBC Type A3) - Tri Antoro, Sutarto; Isfaatun, SE., MM., Eliya; Magdalena, SE., MM., Maria (Accounting, 2009)
Changes in the tobacco excise tax system was instrumental to the achievement of revenue targets for 2009 Budget. Therefore, the effectiveness of changes in the tobacco excise tax system need to be analyzed. This study aims to determine the level of effectiveness of changes in the tobacco excise tax system and to identify strengths, opportunities, weaknesses and threats to change the system in the tobacco excise tax rates KPPBC Type A3 Yogyakarta. This research is a case study conducted in the city of Yogyakarta, especially in KPPBC Type A3 at a time. The study was conducted in KPPBC Type A3 Type A3 because KPPBC is an institution to supervise and care for tobacco excise tax collection. This research period is from April to June 2009. The method of data collection was done by interview, observation and dokmentasi. While data analysis was conducted using quantitative and qualitative methods. Quantitative methods used to determine the effectiveness of changes in the tobacco excise tax system, while the qualitative method of SWOT analysis carried out by weeks to find out the advantages, disadvantages, obstacles and threats from changes in the tobacco excise tax system in KPPBC Type A3. From the quantitative analysis found that tax rates using the new tariff system is more effective to increase the tobacco excise tax revenue KPPBC Type A3. It is known from the increase in tobacco excise tax rates by a total of 19% by using the tariff system the new tobacco excise tax. While the qualitative analysis found that changing the system has strengths that include the existence of a clear legal basis to facilitate monitoring and management of tobacco excise tax, there are opportunities to help achieve the 2009 budget revenue target of the tobacco excise tax sector. In addition to strengths and opportunities there are also weaknesses that create the assumption that the rate for all the tobacco excise tax increases that hinder growth and even resulted in a decrease in production of tobacco. While the threat faced in implementing changes in the tobacco excise tax system, among others, is the attempt by certain manufacturers´ excise tax evasion. Keyword : tobacco, tax, excise